Influence of mechanical damage induced in laboratory on the soil-geosynthetic interaction in inclined-plane shear. (10th October 2018) - Pinho-Lopes, Margarida; Lopes, Maria de Lurdes
Graphical abstract: Highlights: Friction angle of soil-geosynthetic interface increased after mechanical damage. Sliding mechanisms not repeatable; progressive slinging more common after damage. Planar geosynthetics with interface strength lower than geogrid of similar strength. Mechanical damage caused an increase in the skin friction available. Reduction factor for tensile strength conservative to represent interface strength. Abstract: This paper contributes to better understanding how mechanical damage associated with installation affects soil-geosynthetic interaction, particularly for inclined plane shear movement. The mechanical damage was induced in laboratory, adapting a standardised procedure to allow for large samples. Six geosynthetics were studied: two geotextiles, one geocomposite and three geogrids. The soil-geosynthetic interface was characterised using inclined plane shear tests. The laboratory mechanical damage affected the soil-geosynthetic interface strength and the sliding mechanisms observed. The results showed that the mechanical damage caused an increase in the skin friction available, due to the damage mechanisms observed. The structure of the geosynthetic affected the inclined plane shear response after mechanical damage. The friction mobilised in the solid area of the geogrids increased after mechanical damage, which depended on the geogrid and on the consequences of mechanical damage. The reduction factors for mechanical damage associated to installation showed that the interface strength did not change significantly. The reduction factor obtained from tensile tests was, in most cases, conservative to represent the changes observed on the soil-geosynthetic interface strength. The structure of the geosynthetics had a higher impact on their tensile response after mechanical damage than on the soil-geosynthetic interface in inclined plane shear. For the interface strength in inclined shear plane movement, the mechanical damage induced in laboratory of the woven geotextile was conservative compared to field installation damage, while for the woven geogrid the mechanical damage induced in laboratory was within the range of damage induced in the field. Despite some heterogeneity of responses, the standardised laboratory tests to induce mechanical damage in laboratory seem to be able to represent the effect of the mechanical damage associated with installation on the inclined plane shear response of soil-geosynthetic interfaces.